Selection of Refractory Materials for Electric Furnaces Used for Radioactive Waste Vitrification - Sokolov, V. A.; Gasparyan, M. D.; Remizov, M. B.; Kozlov, P. V. (Refractories and industrial ceramics, 2019)
It was shown that fusion-cast chromium-bearing refractories are the most promising when used as the lining material when designing the next generation glass-making electric furnaces and small-sized melters. To ensure a long-term (up to 10 years) service life of the furnace, its elements (e.g., melting tank wall sections at the liquid glass level, partition, overflow zone and sill), which are subject to heavy wear, should be made of KhPL-85 type refractories with high chromium content. Bacor lining of other furnace elements can be replaced for a fusion-cast KhATs-26M type refractory with low chromium oxide content.